The relationship between childhood adversity and problem behavior of new street corner youth on campus: A moderate mediation model - Fan, LinLin; Meng, WeiJie (Frontiers in Psychology, 2022)
To explore the impact mechanism of childhood adversity on problem behavior of new street corner youth on campus, we surveyed 637 new street corner youth on campus completed the Strengths and Difficulties Questionnaire, the Childhood Environment Scale, the Life History Strategies Scale, and the Dark Triad Scale. After controlling for gender and age of new street corner youth on campus, results revealed that childhood adversity was significantly and positively associated with problem behavior. Mediation analysis showed that life history strategy mediated the association between childhood adversity and problem behaviors. Moreover, moderated mediation analysis further indicated that dark triad moderated the association between childhood adversity and life history strategy, as well as the association between life history strategy and problem behavior. These findings suggest that interventions that life history strategy and dark triad may be effective means to affect problem behavior of new street corner youth on campus.